A Systematic Review of Body Fluids Biomarkers Associated With Early Neurological Deterioration Following Acute Ischemic Stroke - Ji, Xiaotan; Tian, Long; Yao, Shumei; Han, Fengyue; Niu, Shenna; Qu, Chuanqiang (Frontiers in Aging Neuroscience, 2022)
Biomarkers are objectively measured biological properties of normal and pathological processes. Early neurological deterioration (END) refers to the deterioration of neurological function in a short time after the onset of acute ischemic stroke (AIS) and is associated with adverse outcomes. Although multiple biomarkers have been found to predict END, there are currently no suitable biomarkers to be applied in routine stroke care. According to the Preferred Reporting Items for Systematic Review standards, we present a systematic review, concentrating on body fluids biomarkers that have shown potential to be transferred into clinical practice. We also describe newly reported body fluids biomarkers that can supply different insights into the mechanism of END. In our review, 40 scientific papers were included. Depending on the various mechanisms, sources or physicochemical characteristics of body fluids biomarkers, we classified related biomarkers as inflammation, protease, coagulation, metabolism, oxidative stress, and excitatory neurotoxicity. The body fluids biomarkers whose related articles are limited or mechanisms are unknown are categorized as other biomarkers. The inflammation-related biomarkers, such as neutrophil-to-lymphocyte ratio and hypersensitive C-reactive protein, play a crucial role among the mentioned biomarkers. Considering the vast heterogeneity of stroke progression, using a single body fluids biomarker may not accurately predict the risk of stroke progression, and it is necessary to combine multiple biomarkers (panels, scores, or indices) to improve their capacity to estimate END.